FACTORS INFLUENCING THE THERMAL CONDUCTIVITY OF CONCRETE: A REVIEW. (International Journal of Food and Nutritional Sciences, 2022)
Concrete is a recognized building material that is utilized extensively in infrastructure projects all around the world. Still, the reduction of natural resources has been obstructed by its extensive use. Researchers have made several attempts to investigate the use of waste materials in concrete as a substitute for natural qualities, in addition to sinking waste disposal difficulties. Essentially, the process of verifying concrete involves determining its strengths, permeability, durability, shrinkage, thermal properties, and other attributes. Of all the thermal qualities of concrete, thermal conductivity (TC) has received the most attention because it depends on the composition of the concrete. Thermal conductivity is a critical metric for assessing a material's capacity to transmit heat in building insulation materials. This paper's goal is to go over the techniques and variables that affect the thermal conductivity (TC) of concrete that contains different kinds of waste materials.